Strategic Communication in Context: Theoretical Debates and Applied Research - Balonas, Sara; Ruão, Teresa; Carrillo, María-Victoria (UMinho Editora, 2021)
Strategic communication is becoming more relevant in communication sciences, though it needs to deepen its reflective practices, especially considering its potential in a VUCA world - volatile, uncertain, complex and ambiguous. The capillary, holistic and result-oriented nature that portrays this scientific field has led to the imperative of expanding knowledge about the different approaches, methodologies and impacts in all kinds of organisations when strategic communication is applied. Therefore Strategic Communication in Context: Theoretical Debates and Applied Research assembles several studies and essays by renowned authors who explore the topic from different angles, thus testing the elasticity of the concept. Moreover, this group of authors represents various schools of thought and geographies, making this book particularly rich and cross-disciplinary.